DAMPAK AKTIVITAS MASYARAKAT TERHADAP TINGKAT PENCEMARAN AIR LAUT DI PANTAI KUTA KABUPATEN BADUNG SERTA UPAYA PELESTARIAN LINGKUNGAN - Elyazar, Nita; Mahendra, M.S.; Wardi, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 2 No 1)
Sea and coastal areas of Badung Regency, especially Kuta Political District is growing rapidly as a tourism area. Increasing community activities created pollution and affected conservation areas, include Kuta Beach. This research aimed to know the positive and negative impacts of community activities of hotels, restaurants, settlement/housing, tradings and services, industries and fisherman. Besides, identification seawater quality of Kuta Beach on their physical, chemical and microbiological parameters during rainy seasons as well as to find out effort on environment conservation done by government and local communities in Kuta Political District. Samples were determined using purposive sampling method collected from three locations at Kuta Beach, which then analysed insite and at analytical laboratory. Seawater quality on their physical, chemical and microbiological parameters ratio was compared with based on standard of seawater quality for marine recreation according to Decree of the State’s Minister Environment Act Number 51 years 2004. The index of the population was then calculated to gain the population index. Samples of community activities were collected using questioner, interview and observation and then analysed by qualitative description method. The result showed that activities at the sea and coastal areas of Kuta Political District had an impact such as increase population and job availability, provision of income to Badung Regency and Tradition Village, environment aesthetics, perception of community, culture and region perform, waste and environment sanitation, land use degradation of coastal border, mobility of motorized vehicle and seawater intrusion. The water quality of Kuta Beach during rainy seasons in February year 2006 exceeded the threshold level or quality standard such as rubbish, NH3, NO2, NO3, PO4, Cu, Cd, Pb, E. coli and coliform. DO exceeded the minimum limits of seawater quality standard. Whereas, parameters which did not yet exceed the maximum limits namely: temperature, colour, smell, turbidity, TDS, salinity, pH, BOD, COD, fat and oil, fenol, Hg and Fe. The result showed that score of calculation pollution index of Kuta Beach seawater in three research zone, were between 6,46 and 6,77. The effort on environment conservation in Kuta Political District had been conducted by local community and government, but long term effort in environment conservation is still needed better strategy and actions in an integrated and sustainable manners.
Keywords: community activities, impact, seawater quality, pollution index, conservation effort.